Sulphostin-inspired N-phosphonopiperidones as selective covalent DPP8 and DPP9 inhibitors - Leonard Sewald; Werner W. A. Tabak; Lorenz Fehr; Samuel Zolg; Maja Najdzion; Carlo J. A. Verhoef; David Podlesainski; Ruth Geiss-Friedlander; Alfred Lammens; Farnusch Kaschani; Doris Hellerschmied; Robert Huber; et al. (Nature Communications)
Abstract Covalent chemical probes and drugs combine unique pharmacologic properties with the availability of straightforward compound profiling technologies via chemoproteomic platforms. These advantages have fostered the development of suitable electrophilic “warheads” for systematic covalent chemical probe discovery. Despite undisputable advances in the last years, the targeted development of proteome-wide selective covalent probes remains a challenge for dipeptidyl peptidase (DPP) 8 and 9 (DPP8/9), intracellular serine hydrolases of the pharmacologically relevant dipeptidyl peptidase 4 activity/structure homologues (DASH) family. Here, we show the exploration of the natural product Sulphostin, a DPP4 inhibitor, as a starting point for DPP8/9 inhibitor development. The generation of Sulphostin-inspired N-phosphonopiperidones leads to derivatives with improved DPP8/9 inhibitory potency, an enhanced proteome-wide selectivity and confirmed DPP8/9 engagement in cells, thereby representing that structural fine-tuning of the warhead’s leaving group may represent a straightforward strategy for achieving target selectivity in exoproteases such as DPPs.